The Divided House: Does Racial Segregation Predict Far-Right Protest in United States Metropolitan Areas? - Gibbons, Joseph (Race and social problems, 2025)
In recent years, there has been dramatic growth in far-right protests in metropolitan areas across the United States. This study investigates whether residential segregation by race/ethnicity predicts this protest, even when considering pertinent contemporary issues ranging from response to the Black Lives Matter movement to the impact of COVID-19. We identify far-right protests using data from the Armed Conflict Location & Event Data project, an effort to document instances of mass protest in metropolitan areas. We measure metropolitan segregation and relevant demographics with the 2015–2019 pooled wave of the American Community Survey. We also employ a variety of novel datasets to account for contemporary issues like physical distancing during the COVID-19 pandemic. Findings reveal the overall degree of segregation, as measured by evenness, can have a significant and robust association with far-right protest. However, these associations depend on the racial character of the segregation.